RANGKAP JABATAN PRESIDEN SEBAGAI KETUA PARTAI POLITIK DALAM SISTEM KETATANEGARAAN INDONESIA - Fudika, Moza Dela; Indra, Mexsasai; ', Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Dual position of president as the head of a political party is the practice ofgovernance that has existed since the early days of Indonesian independence.President prohibition setting for concurrent positions in any public office has actuallybeen set explicitly in the constitution of RIS and the Provisional Constitution 1950.But such arrangements are no longer contained in the application of the Consitution1945. Government system Indonesian is now a presidential system. If the presidentdoubled as head political party, that would result in the instability goverment. Besidesee where political parties are dysfunctional resulting in worsening theimplementation of the wheels of government and no longer in accordance with thegeneral principles of good governance. So that the necessary rules for the presidentialban concurrently. Therefore required political study of law by law makers toduplicate the legal establishment of the post the president who poured into the law.Keywords : Double Position – President – Leader of the Political Party